Numerical study on the ratcheting performance of rail flash butt welds in heavy haul operations. (1st June 2021) - Su, Hang; Pun, Chung Lun; Mutton, Peter; Kan, Qianhua; Kang, Guozheng; Yan, Wenyi
Highlights: A first approach to evaluate ratcheting performance of rail flash butt welds is presented. The numerical study combined a dynamic wheel–rail weld rolling contact simulation, multiple quasi-static wheel–rail weld contact simulations and a cyclic loading simulation. The weld region was divided into 23 zones due to various mechanical properties across the rail weld. The region with the lowest hardness in the softened zone has the shortest RCF initiation life. RCF is likely to initiate more deeply in the softened zone than the parent rail and the region around the bond line. Abstract: The ratcheting performance of a new R400HT rail flash butt weld was numerically evaluated under a typical heavy haul in-service condition. Due to varying mechanical properties across the rail weld, the weld region was divided into 23 zones in the numerical study. A dynamic finite element simulation of wheel–rail weld rolling contact was first carried out to obtain the total vertical contact force and its variation along rolling distance. Multiple quasi-static wheel–rail weld contact simulations were then performed by applying the total vertical contact force to determine the non-Hertzian contact pressure distribution when the wheel was located at different positions across the weld in the rolling direction. Based on each normal contact pressure distribution, the Haines and Ollerton's strip theory and Carter's theory were employed to estimate the corresponding longitudinal surface tangential traction distribution. Finally, a cyclic loading simulation was conducted to evaluate the ratcheting performance of the rail weld in terms of RCF initiation life by repeatedly translating these normal contact pressure and longitudinal tangential traction distributions on the running surface. The results reveal that the subzone with the lowest hardness in the softened zone has the shortest RCF initiation life among the weld region, followed by the region around the bond line. The parent rail provides the longest RCF initiation life and therefore has the best resistance to RCF. Additionally, the existence of the softened zone can shorten the RCF initiation life of the parent rail and the bond line section, particularly the regions located adjacent to the softened zone. The possible location of RCF initiation in the softened zone of the rail head can reach deeper than those in the parent rail and the region around the bond line. The results can help us understand the failure of flash butt rail welds in heavy haul operations and the numerical method can be applied to study different rail welds and rail welds under different conditions such as in a curved track. Graphical abstract: Image, graphical abstract